2015
DOI: 10.1097/shk.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Attenuates Renal Injury In A Swine Model Of Neonatal Hypoxia-Reoxygenation

Abstract: Acute kidney injury in asphyxiated neonates is common. The renal protective effects of doxycycline, a known matrix metalloproteinase (MMP) inhibitor, have been demonstrated in rat ischemic-reperfusion models of injury. These effects have not been tested in large-animal models designed to reflect true clinical scenarios of neonatal hypoxia-reoxygenation (H-R). Newborn piglets were surgically instrumented for hemodynamic monitoring and subjected to 2 h of hypoxia followed by 4 h of normoxic reoxygenation. Piglet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…Its protective effect in neonates against AKI induced by H-R or I-R is largely unknown. Previously, we also demonstrated that post-resuscitation administration of DOX attenuated AKI associated with the inhibition of MMP-2 activity in newborn piglets with severe H-R (18). Despite providing functional and biochemical data for the beneficial effects of DOX in neonatal H-R, the short time course (4 h after reoxygenation) precludes us from understanding if the renal protection of DOX will persist beyond the acute stage.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Its protective effect in neonates against AKI induced by H-R or I-R is largely unknown. Previously, we also demonstrated that post-resuscitation administration of DOX attenuated AKI associated with the inhibition of MMP-2 activity in newborn piglets with severe H-R (18). Despite providing functional and biochemical data for the beneficial effects of DOX in neonatal H-R, the short time course (4 h after reoxygenation) precludes us from understanding if the renal protection of DOX will persist beyond the acute stage.…”
Section: Introductionmentioning
confidence: 77%
“…Piglets were block-randomized into two treatment groups ( n = 8/group) and subjected to an 1-h period of normocapnic hypoxemia (FiO 2 of 0.11–0.15) followed by a 4-h period of normoxic reoxygenation (FiO 2 of 0.21–0.25). Five minutes into reoxygenation piglets received an intravenous bolus of either 1 mL normal saline (saline-control group) or 30 mg/kg DOX (DOX group), an optimal dose based on our previous study (18), blindly . Five sham-operated piglets underwent surgery with no hypoxia and reoxygenation at a FiO 2 of 0.21–0.25.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans as well as animals can be exposed to hypobaric (HH) or normobaric hypoxia (NH) in order to study wide variety of diseases, including pulmonary hypertension (20), reoxygenation injury (21), pre-eclampsia (22), hypoxic insult of the brain (23), and diabetic retinopathy (24). While HH, which physically resembles a high-altitude environment, is induced by decreasing atmospheric pressure under 101 325 Pa (1 atm, 760 mm hg) typically in a tightly sealed hypobaric chamber (25), NH exposure is based on the reduction of the partial pressure of oxygen (pO 2 ) at normal atmospheric pressure, which typically occurs through the administration of nitrogen to a face mask (26), hypoxic tent (27), or environmental chamber (22,23).…”
Section: In Vivo Models Of Hypoxiamentioning
confidence: 99%
“…Sonuçta doksisiklinin renal perfüzyonu arttırdığı, renal hasarı hafiflettiği ve MMP-2 aktivitesini ve doku oksidatif stresi azalttığı gösterilmiştir [57] .…”
Section: Kardiyoprotektif Etkiunclassified